Survival strategies of informal sector workers in Bali's tourism industry - Ni Made Ary Widiastini; Ida Bagus Adi Laksana; Putu Indah Rahmawati; Trianasari Trianasari; Made Aristia Prayudi (Journal of Applied Sciences in Travel and Hospitality, 2024)
The informal tourism sector plays a vital role in the local economies, particularly in destinations such as Bali. This aligns with the United Nations Sustainable Development Goal 8, which focuses on promoting decent work and economic growth. These workers, who are often ignored, greatly enrich the experience of tourism but encounter distinct obstacles on a daily basis. Gaining insight into their methods for staying alive is crucial. Informal workers face distinct limits compared to formal sector employees, resulting in less defined sustainability and growth strategies. A thorough investigation was carried out in nine regencies in Bali, utilizing observations and interviews, in order to examine these tactics. This method facilitated a comprehensive comprehension of their day-to-day routines and difficulties. The study identified four crucial survival strategies: implementing prudent financial management to sustain businesses and meet daily needs, utilizing communication skills to maintain income and continuity, enhancing social capital through positive relationships with fellow workers, and comprehending government policies. Out of these factors, effectively managing economic capital is crucial for maintaining livelihoods in the fiercely competitive tourism business. The results of this study provide a basis for future policies or interventions aimed at supporting and enhancing the lives of informal sector workers in tourist areas such as Bali.